The Implementation of Integrated Islam School Curriculum (SIT) at SDIT Bina Insani Kediri - Febriana Triastuti (Didaktika Religia, 2017)
This article describes the implementation of the Integrated Islamic School curriculum and its concept in the Integrated Islamic Primary School (SDIT) Bina Insani Kediri. This research uses qualitative approach. Data collection procedures in this study are observation, interviews, and documentation. There is a difference between PENDIKNAS curriculum and the Integrated Islamic School curriculum (SIT) in terms of content, implementation strategies and evaluations. The curriculum of Integrated Islamic School (SIT) is a combination of National Education curriculum and the uniqueness of Integrated Islamic School (SIT). The implementation is done by internalizing Islamic values into learning materials, activities, and rules and norms.